Financial and Legal Constraints to Growth: Does Firm Size Matter? - BECK, THORSTEN; DEMIRGÜÇ‐KUNT, ASLI; MAKSIMOVIC, VOJISLAV (Journal of Finance, 2005)
ABSTRACT Using a unique firm‐level survey database covering 54 countries, we investigate the effect of financial, legal, and corruption problems on firms' growth rates. Whether these factors constrain growth depends on firm size. It is consistently the smallest firms that are most constrained. Financial and institutional development weakens the constraining effects of financial, legal, and corruption obstacles and it is again the small firms that benefit the most. There is only a weak relation between firms' perception of the quality of the courts in their country and firm growth. We also provide evidence that the corruption of bank officials constrains firm growth.